Examining the Impact of Strategic Alignment of Information Technology on International Success with the Mediating Role of Strategic Agility in Small and Medium-Sized Enterprises - Hamzah Mohaisen, Sabah; Rahimiaghdam, Samad; Hosseini, Seyed Samad; Ahmadian, Vahid (Digital Transformation and Administration Innovation, 2025)
International success is critical for SMEs to achieve growth and access new markets. This study investigates the impact of strategic alignment of information technology on international success in small and medium-sized enterprises (SMEs), with a focus on the mediating role of strategic agility. The present study was a descriptive-survey research. The population consisted of 32,000 companies in Tabriz and 23,000 companies in Karbala, from which a sample of 384 companies was selected using Cochran's formula and random sampling method. Data were collected through a questionnaire. The collected data were analyzed using structural equation modeling (SEM) through AMOS software. The results showed that strategic alignment of information technology has a significant effect on international success and strategic agility in SMEs. Moreover, strategic agility has a significant impact on international success in SMEs.